Librarians’ Digital Competencies: Influence on their Utilization of Emerging Educational Technologies (British Journal of Multidisciplinary and Advanced Studies, 2023)
Academic and instructional services in academic institutions, particularly in Higher Education Institutions (HEIs), have changed as a result of technological advancement. Library and information search services are being digitized, and librarians must gain digital skills in order to provide library users with more effective and efficient research services. The purpose of this study was to determine the influence of librarians’ digital competencies in their utilization of emerging educational technologies. This study used the descriptive correlational research design and analyzed using descriptive and inferential statistics. The participants were eighty (80) registered librarians and active Philippine Librarians Association, Inc. (PLAI) members who are employed in selected libraries in Northern Mindanao. Online survey questionnaires were used for data collection. Findings reveal that the librarians’ digital competencies in terms of managing and developing digital libraries were high. while the competencies in protecting digital content were rated to a moderate extent. Moreover, the librarians’ extent of utilization of emerging educational technologies in terms of cloud computing, web conferencing, and institutional repositories was rated as generally high. The librarians’ assessment of their digital competencies significantly influence their utilization of emerging educational technologies. It is concluded that the digital competencies of librarians are crucial and indispensable as it influences their utilization and application of emerging technologies in managing and developing digital library services. It is recommended that the librarians may acquire knowledge and skills, particularly on these topics related to protecting digital contents: computer and network security, security tools and techniques, digital copyright policy, copyright issues and security and privacy in digital libraries.